Perancangan Mesin Milling untuk Pembuatan Plat Dwikutub pada Teknologi Fuel Cell - Putra, Aldiansyah; Malau, Vicky Frans; Lumbantoruan, Jhonatan; Iswandi, Iswandi (CV. IRA PUBLISHING, 2025)
This research aims to design and test the performance of a CNC-based mini milling machine as a lightweight milling solution at a relatively affordable cost. The research stage is carried out systematically, starting with the selection of concepts and proceeding through morphological table analysis, followed by the component manufacturing process, which utilizes CNC turning machines to ensure dimensional precision. After that, the main components were assembled, including aluminum tables, stepper motors, trapezoidal threads, DC motor spindles, and support frames that function to maintain structural stability. The tests focus on the stability of axis motion and the precision level of cutting light materials. The test results indicate that the CNC machine operates within acceptable tolerances, is stable enough, and precise for simple cutting applications, making it suitable for use in engineering education and small-scale production, with good operational efficiency.